Social inclusion policy effects on democratic satisfaction in Europe: a catalyst of polarization threating the identities of privileged social groups - Akinyemi, Ibrahim Olayinka; Groß, Martin; Lang, Volker (Frontiers in Sociology, 2025)
This study analyses the influence of inclusive policies on the democratic satisfaction of different social groups. It draws on social identity theory to explain how inclusive policies can contribute to conflicts and polarization in attitudes between social groups. More specifically, inclusive policies aim to improve the rights and social recognition of disadvantaged groups while they reduce the privileges of groups traditionally recognized as superior. Consequently, we expect that democratic institutions (as the providers of these policies) either get support or disproval from the respective social groups for inclusive policies—causing related increases and decreases in the democratic satisfaction of the respective groups. Using longitudinal data from European Social Survey (rounds 1–10) and additional country level data, we test how socially inclusive policies affect differences in democratic satisfaction between disadvantaged and privileged groups in four policy areas: (1) religious freedom, (2) inclusion of migrants, (3) equal treatment of homosexuals, and (4) gender equality. Except for gender equality policies, our findings support our hypothesis: socially inclusive policies lead to less democratic satisfaction for groups traditionally recognized as superior while the democratic satisfaction of formerly disadvantaged groups increases. These changes in democratic satisfaction indicate that inclusive policies lead to gains in equal social recognition (Isothymia) for some but at the same time are considered a threat to privileged social recognition (Megalothymia) by others. With respect to support for (democratic) political institutions inclusive policies are therefore a “double-edged sword” and need to be implemented with care. However, given comparatively strong inclusive policies regarding religious freedom and migrant integration our analyses also indicate convergence in democratic satisfaction between disadvantaged and privileged social groups.